The Construction of the Female Hero in Zusak’s The Book Thief: An Archetype Analysis - Sintia Ayu Ningsih; Rahayu Puji Haryanti (LPPM Universitas Advent Indonesia, 2026)
Heroic narratives in literature traditionally tend to be dominated by male characters with physical strength, dominance, and victory characteristics. In contrast, female characters often serve as passive and domestic roles. This study examines the construction of a female hero in Markus Zusak's The Book Thief through Christopher Vogler's (2007) archetypes and the hero's journey. Using a qualitative approach, this study reveals how the character Liesel Meminger builds her heroic identity through courage, empathy, and literacy in the middle of the Nazi regime's oppression. The findings show that Liesel represents a heroine who prioritizes emotional resilience and the power of words over physical strength. Other archetypes support her and follow the twelve stages of the hero's journey. The novel actively challenges traditional hero archetypes by presenting a heroic narrative that ends in loss, not victory, but is still full of meaning and strength. This research enriches literary and gender studies by highlighting the representation of female heroes in contemporary fictional narratives.